2012
DOI: 10.1590/s1413-35552012005000012
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação das adaptações transculturais e propriedades de medida de questionários relacionados às disfunções do ombro em língua portuguesa: uma revisão sistemática

Abstract: Objectives: To evaluate the quality of the adaptation procedures as well as the clinimetric testing of the shoulder disability questionnaires available in Portuguese that has occurred for each adaptation. Methods: Systematic literature searches on MEDLINE, EMBASE, CINAHL, SCIELO and LILACS were performed to identify relevant studies. Data on the quality of the cross-cultural adaptation procedures and clinimetric testing were extracted. All studies were evaluated according to the current guidelines for cross-cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 28 publications
1
31
0
6
Order By: Relevance
“…32 It is also necessary to test the measurement properties of the translated instruments, even if they have already been tested for the original questionnaires, as cultural differences between distinct populations may affect these properties. 44 Our research group previously conducted a systematic review 40 of the cross-cultural adaptation and measurement properties of questionnaires related to shoulder disorders available in Portuguese. This review identified 7 instruments translated and adapted into Brazilian Portuguese (the DASH, SPA-DI, Western Ontario Rotator Cuff Index, Penn Shoulder Score, American Shoulder and Elbow Surgeons questionnaire, University of California, Los Angeles Shoulder Rating Scale, and Athletic Shoulder Outcome Rating Scale).…”
Section: T T Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…32 It is also necessary to test the measurement properties of the translated instruments, even if they have already been tested for the original questionnaires, as cultural differences between distinct populations may affect these properties. 44 Our research group previously conducted a systematic review 40 of the cross-cultural adaptation and measurement properties of questionnaires related to shoulder disorders available in Portuguese. This review identified 7 instruments translated and adapted into Brazilian Portuguese (the DASH, SPA-DI, Western Ontario Rotator Cuff Index, Penn Shoulder Score, American Shoulder and Elbow Surgeons questionnaire, University of California, Los Angeles Shoulder Rating Scale, and Athletic Shoulder Outcome Rating Scale).…”
Section: T T Resultsmentioning
confidence: 99%
“…Most of its measurement properties have already been tested on the Brazilian population in patients with shoulder disorders. 40 The QuickDASH is composed of 11 questions, compared to the 30 questions of the extended version, and is more practical to use due to its shorter completion time. 4 To our knowledge, the measurement properties of the QuickDASH had not yet been tested in a Brazilian population prior to this study.…”
Section: Discussionmentioning
confidence: 99%
“…The criteria used to assess the adaptation process in this review are well described in protocols and manuals (7) and have been used in conducting systematic reviews of measuring instruments in different contexts, such as assessment of pain (10) and shoulder dysfunction (27) .…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review showed that there are seven questionnaire for this purpose (DASH, WORC, SPADI, PSS, ASORS, ASES e UCLA). 6 However, no prospective assessment tool specifically for the shoulder, such as the Shoulder Rating Questionnaire (SRQ), has been translated in accordance with the appropriate methodological rigor of validation for the Brazilian Portuguese language.…”
Section: Introductionmentioning
confidence: 99%